THE INFLUENCE OF PRINCIPAL TRANSFORMATIONAL LEADERSHIP AND COMPENSATION ON TEACHER PERFORMANCE AT SMKS INDONESIA RAYA BANDUNG - Dudun Junaedi (Journal Informatic, Education and Management (JIEM), 2026)
The study examines how principal transformational leadership and compensation affect teacher performance at SMKS Indonesia Raya Bandung. A quantitative survey design was used. All 45 teachers at the school were included (census sampling). Data were gathered via Likert 1–5 questionnaires and analyzed with multiple regression (SPSS). Findings: (1) Transformational leadership had a positive, significant effect on teacher performance (β = 0.342; p < 0.05); (2) Compensation had a positive, significant effect on teacher performance (β = 0.298; p < 0.05); (3) Both variables jointly had a positive, significant effect (F = 25.847; p < 0.05; R² = 0.547), explaining 54.7% of the variance in teacher performance. Implications: principals should strengthen transformational leadership and the school should review its compensation system to enhance teacher performance